Salmonella gastroenteritis outbreak in a family: a case report - Adhikari, Sunil; Rijal, Suraj; Shrestha, Ashish (Journal of Patan Academy of Health Sciences, 2019)
Five members of a family were brought to emergency with complaints of high grade fever, pain abdomen, diarrhoea and vomiting. The symptoms started after five hours of food, the vegetable curry by this family. Four of them were in hypovolemic shock and two had significant pus cells in stool examination. All of them were discharged by seven days. Stool culture of three of these patients showed salmonella.